2021
DOI: 10.3390/ani11082438
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Inulin Source and a Probiotic Supplement in Pig Diets on Carcass Traits, Meat Quality and Fatty Acid Composition in Finishing Pigs

Abstract: In this experiment, we investigated the effect of the supplementation of probiotic bacteria in the diet with inulin or dried Jerusalem artichoke tubers on the performance, meat quality, and fatty acid composition in the meat and backfat of fatteners. One hundred and forty-four crossbred pigs (PIC × Penarlan P76) were divided into six groups and fattened from 30 to 114 kg. The meat proximate composition, pH, color, texture, shear force, water-holding capacity, sensory attributes, and thiobarbituric-acid-reactiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 52 publications
2
13
0
1
Order By: Relevance
“…There is insufficient evidence to confirm that dietary prebiotics and probiotic supplementation effectively alter tissue fatty acid profiles. For example, longissimus dorsi muscle fatty acid profile did not change following the addition of inulin and horse chestnuts [ 62 ]. However, the inclusion of inulin into rabbit diets has resulted in an increase in linoleic acid and omega-3-PUFA levels, as well as a decrease in the indices of atherogenicity and thrombogenicity [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…There is insufficient evidence to confirm that dietary prebiotics and probiotic supplementation effectively alter tissue fatty acid profiles. For example, longissimus dorsi muscle fatty acid profile did not change following the addition of inulin and horse chestnuts [ 62 ]. However, the inclusion of inulin into rabbit diets has resulted in an increase in linoleic acid and omega-3-PUFA levels, as well as a decrease in the indices of atherogenicity and thrombogenicity [ 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…In 2004, Hansen et al [ 46 ] reported that the sensory quality of pork was influenced by the manipulation of feed ingredients, including fructooligosaccharides, but in this study, finishing pigs that received a synbiotic glyconutrient supplement revealed a higher sensory profile of tenderness and juiciness (pork belly meat) and strong flavor (loin meat). On the other hand, Grela et al [ 47 ] found less hardness of meat by dietary pre (inulin)-and probiotics ( Lactococcus lactis , Carnobacterium divergens , Lactobacillus casei Lactobacillus plantarum and Sacharomyces cerevisiae ). The reason for the increased tenderness and juiciness of belly and loin meat are probably due to the presence of fat which enhances WHC by lubricating the muscle fibers during cooking and increasing the tenderness of meat to reveal the sensation of juiciness [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…From these observations, the benefits of prebiotics are usually attributable to the following aspects: (a) stimulating beneficial bacteria and SCFAs production and, accordingly, improving barrier function, and anti-inflammatory stimuli; and (b) decreasing levels of some pathogenic organisms (such as Defluviicoccus and Gardnerella ) that cause gut dysbiosis. Additionally, prebiotics can modulate lipid metabolism and result in a higher IMF level in finishing pigs [ 142 ], possibly by inhibiting lipogenic enzymes activity, and subsequently reducing production of lipoproteins and TGs [ 143 ]. In brief, the action of prebiotics is exerted via altering the certain bacteria abundance and the metabolites that are produced.…”
Section: Factors Affecting Gut Microbial Composition and Functionmentioning
confidence: 99%